Role of Ecosystem Services by Bats in Crop Pest Management: Modeling, Analysis and Simulation - Kumari, Medha; Tandon, Abhinav; Dutta, Vaishnudebi; Namagiri, Mukul (Discontinuity, Nonlinearity, and Complexity, 2026)
The delicate interplay among agricultural ecosystems, insect pest populations, and natural predators is a complex phenomenon that significantly influences sustainable crop management. This work uses a mathematical model to investigate the intricate dynamics governing the interrelationship that involves population densities of bats, crop biomass, and insect pests. The model is grounded in a nonlinear system of ordinary differential equations to unveil the nuanced mechanism underpinning the complex nexus that controls the coexistence of bats, crop biomass, and insect pests. The mathematical model analyses the dynamics and identifies conditions for system stability. The numerical simulation results serve as evidence for the conclusions drawn. The outcomes of the study indicate that when bats cohabited with crops and insect pests at their maximum density, the agricultural system stabilizes. It underscores the pivotal role assumed by bats as natural predators, wielding a substantial influence in the regulation of insect pest populations and, consequently, in the preservation of crop biomass density.